Dampak Sleepcall Terhadap Kesejahteraan Mental Mahasiswa Tingkat Akhir - Putri, Nabila Mailina (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2025)
This study aims to investigate the impact of sleepcall on the psychotic condition of final year students at the Islamic University of Majapahit. Sleepcall is a phenomenon that is generally used by students in maintaining long-distance relationships. However, the impact of sleepcalling on the mental health of final year students is not fully understood, which can lead to sleep, motivation, and concentration problems. This study uses quantitative methods to collect empirical data with certain validity. The results showed that sleep calling and anxiety levels had a significant impact on the mental health of final year students at Majapahit Islamic University, contributing 24.2% to their psychological condition. Sleepcall activity has a close relationship with students' current state of psychosis, demonstrating the importance of sleepcalling in influencing their mental health and well-being. This study also found that Sleepcall had a positive impact on the mental health of final year students by reducing stress levels and impacting the overall psychological condition.